Faktor-Faktor Yang Mempengaruhi Tingkat Underpricing Saham Pada Perusahaan Yang Melakukan Initial Public Offering Yang Terdaftar Di Bursa Efek Indonesia - Viriany Jodin; Mega Gunawan (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2015)
The purpose of this study is to obtain empirical evidence of return on assets, debt to equity ratio, earnings per share, firm age, firm size and the percentage of stock offering to the public of the level of underpricing of shares in a company which do initial public offering in Bursa Efek Indonesia. The population in this study is all companies that do an initial public offering listed in the Bursa Efek Indonesia with a period of 2007 to 2012, which amounted to 125 companies that obtained through field studies in Bursa Efek Indonesia. Samples are selected by using the purposive sampling method amounted to be 66 companies. The method of analysis in this study uses multiple regression analysis. The purpose to through analysis multiple regression is to prove the effectiveness of each six variables on the level of underpricing. The results of this study showed that return on assets and firm size have a significant influence on the level of underpricing.